Pancasila sebagai Sistem Hukum - Rosa Suhaeni; Pingkan Wardhani; Putri Puspitasari; Riska Andi Fitriono (Gema Keadilan, 2022)
During its development period, Pancasila has provided values that are useful for the survival of the Indonesian nation and state.  However, the usefulness is not entirely real.  This can be seen in the Indonesian regulatory system, which until now still maintains the pluralism of the legal system.  The reality of this legal system pluralism is a situation that reflects that Pancasila in the legal system does not fully have real and concrete usefulness.  In addition, in achieving legal goals, it is still influenced by two schools of legal thought which in principle contradict each other, namely legal positivism which prioritises legal certainty and legal realism which seeks the substance of justice.  Therefore, Pancasila must clearly show real and concrete useful values in the Indonesian legal system.